Mini-fábrica: uma nova proposta de arranjo produtivo e organizacional híbrido em uma empresa do setor eletroeletrônico. - Rotta, Ivana Salvagni (2004)
This thesis is concerned to the structure of a productive and organizational arrangement the mini-factory (MF) and its related concepts. A local subsidiary of an electronics multinational corporation was analysed, considering the main characteristics of the mini-factory. The thesis analysed the initial project for the mini-factory, its planning and implementation, the main changes and adaptations along the years, and the way that the mini-factory concept is used more recently by the company. The thesis also analysed the mini-factory impacts and contributions for the work groups and the qualification processes, focusing both people and organization. A case study research was developed, including interviews and data research, considering three distinctive periods of study. The variety of data collected supported the analysis of several important characteristics of the company and the way it works. The main results of this thesis show that the arrangement studied, called mini-factory by the company, is, actually, a new hybrid productive and organizational arrangement, that integrates characteristics of the mini-factory original concept with the related concepts. The results indicate that the adaptation processes, made during the years by the company, developed an arrangement different from those described by the other companies and even by the literature. These identified characteristics had been crucial for the good results achieved by the company and, nowadays, it is considered an example for the other subsidiaries of this multinational corporation.